Strength and Wear Behavior of Three-Dimensional Printed and Prefabricated Denture Teeth: An In Vitro Comparative Analysis - Gad, Mohammed M.; Alalawi, Haidar; Akhtar, Sultan; Al-Ghamdi, Raghad; Alghamdi, Rahaf; Al-Jefri, Alaa; Al-Qarni, Faisal D. (European Journal of Dentistry, 2023)
Objectives With advanced technology for complete denture fabrication, there is a lack of knowledge on the mechanical behavior of three-dimensional (3D) printed teeth despite the development of complete denture fabrication technologies. This study aimed to compare different types of 3D-printed teeth in terms of wear and fracture resistance in comparison to control prefabricated denture teeth.Materials and Methods One prefabricated tooth was selected and fixed in a resin holder and half of the tooth remained in anatomic form, while the other half was flattened for the wear test. One from each type was scanned and then printed with different resins; Asiga (DentaTOOTH, Asiga, Alexandria 2015,NSW, Australia), FormLabs (Denture Base LP, FormLabs, Berlin, Germany), and NextDent (NextDent C&B MFH, NextDent B.V., Soesterberg, the Netherlands) according to manufacturer recommendations. A total of 60 specimens (20/resin, n = 10) were thermo cycled (5,000 cycles) and wear test samples were further subjected to cyclic loading (1,70,000 cycles) in a chewing simulator machine CS-4.2 (SD Mechatronik GmbH, Germany). The fracture strength of anatomic teeth was measured using a universal testing machine (Instron model 5965, Massachusetts, United States), while Geomagic Control X software was used to assess the amount of wear of flattened teeth. Statistical analyses were performed with one-way analysis of variance with Tukey's post hoc test at significance level of α = 0.05.Results NextDent specimens showed the greatest volume loss, whereas FormLabs specimens showed the least volume loss. Comparing NextDent specimens to FromLabs specimens, FromLabs showed statistically significantly less volume loss (p < 0.001). No other group pairs differed significantly from one another in terms of volume loss (p > 0.06).Conclusion 3D-printed denture teeth showed comparable strength and wear resistance with the prefabricated denture teeth and were suitable for long-term clinical usage except for NextDent that significantly showed the lowest fracture resistance.
Keywords: 3D printing; prefabricated teeth; complete denture; mechanical testing